дидактические материалы алгебра 7 класс Звавич, Кузнецова

Вариант 2

с-33

 

1. 1) a) (х + 4)(у - 5) = ху - 5х + 4у - 20;
б) (х - 8)(6 - у) = 6х - ху - 48 + 8у;
в) (-10 - x)(у + 3) = -10у - 30 - ху - 3х;
г) (-2 - y)(x - 9) = -2х + 18 - ху + 9у;
2) а) (а + 3)(а - 4) = а2 - 4а + 3а - 12 = а2 - а - 12;
б) (а - 1)(6 - а) = 6а - а2 - 6 + а = -а2 + 7а - 6;
в) (5 + а)(-а - 2) = -5а - 10 - а2 - 2а = -а2 - 7а - 10;
г) (-а - 1)(а - 7) = -а2 + 7а - а + 7 = -а2 + 6а + 7;
3) а) (5а - 7)(3а + 1) = 15а2 + 5а - 21а - 7 = 15а2 - 16а - 7;
б) (3b + 7)(4 - 3b) = 12b - 9b2 + 28 - 21b = -9b2 - 9b + 28;
в) (2х - 3y)(x + 2у) = 2x2 + 4ху - 3xy - 6y2 = 2x2 + ху - 6у2;
г) (12а + 11)(-10 - 5а) = -120а - 60а2 - 110 - 55а = -40а2 - 175а - 110;
4) а) (5а2 + 1)(3y - 1) = 15а2у - 5а2 + 3у - 1;
б) (5y2 + 1)(3y2 - 1) = 15y4 - 5y2 + 3y2 - 1 = 15y4 - 2y2 - 1;
в) (а2 + b)(а - b2) = а3 - а2b2 + ab - b3;
г) (а2 - b)(а - b2) = а3 - а2b2 - аb + b3;
5) а) (x + 3)(x2 - x - 1) = x3 - x2 - x + 3x2 - 3x - 3 = x3 + 2x2 - 4x - 3;
б) (7у - 1)(у2 - 5у + 2) = 7у - 35y2 + 7у - у2 + 5у - 1 = 7у3 - 36y2 + 12y - 1;
в) (а + b - 1)(b + а) = ab + а2 + b2 + ab - b - a = a2 + 2ab + b2 - b - a;
г) (a + 3b)(a - 3b - 1) = a2 - 3ab - a + 3ab - 9b2 - 3b = a2 - 9b2 - a - 3b;
6) a) 5(x + 2)(x + 3) = 5x2 + 15x + 10x + 30 = 5x2 + 25x + 30;
6) -6(a + 4)(a - 1) = -6a2 + 6a - 24a + 24 = -6a2 - 18a + 24; 
в) с(2 + 3с)(5с - 1) = 10c2 - 2c + 15c3 - 3c2 = 15c3 + 7c2 - 2c; 
г) 3b(b - c)(c + 4b) = 3b2c + 12b3 - 3bc2 - 12b2c = 12b3 - 9b2c - 3bc2.

2. 1) a) (x2 + x - 1)(x2 - x + 1) = х4 - х3 + х2 + х3 - х2 + х - х2 + х - 1 = x4 - x2 + 2x - 1;
б) (2m2 + 3m + 1)(-2m2 + 3m - 1) = -4m4 + 6m3 - 2m2 - 6m3 + 9m2 - 3m - 2m2 + 3m - 1 = -4m4 + 5m2 - 1;
2) a) (c - 1)(c4 - c3 + c2 - c + 1) = c5 - c4 + c3 - c2 + c - c4 + c3 - c2 + с - 1 = с5 - 2c4 + 2c3 - 2c2 + 2c - 1;
б) (4 - у + у2 - у5)(1 - у) = 4 - 4у - у + у2 + y2 - у3 - у5 + у6 = y6 - y5 - y3 + 2y2 - 5y + 4;
3) a) (x + 5)(x - 2)(x2 - 3x - 10) = x4 - 3x3 - 10x + 3x3 - 9x2 - 30x - 10x2 + 30x + 100 = x4 - 29x2 + 100;
6) (y - 1)(y2 + y + 1)(у6 + y3 + 1) = (y3 - 1)(y6 + y3 + 1) = y9 - 1.

3. (2a - 4b)(3a - 8b) = (4b - 2a)(8b - 3a) = 2(2b - a)(8b - 3a).

4. a)(y + 1)(y - 3) = y2 - 2y - 3; 6) (x - 5)(x + 4) = x2 - x - 20.